LAW ENFORCEMENT AGAINST PIMPS IN UNDERCOVER PROSTITUTION THROUGH "PLUS" MASSAGE PARLORS - Ardan, Andra; DM, M. Yusuf; Pardede, Rudi (JILPR Journal Indonesia Law and Policy Review, 2025)
Clandestine prostitution through massage parlors in the jurisdiction of Polresta Pekanbaru exemplifies how social crimes have evolved over time by exploiting regulatory loopholes. This form of prostitution is concealed under the guise of legitimate massage or spa services, making it difficult for law enforcement agencies to detect. In reality, these services involve sexual activities managed by pimps. The aim of this study is to analyze law enforcement efforts against pimps involved in clandestine prostitution in massage parlors within the jurisdiction of Polresta Pekanbaru, to identify the obstacles hindering such enforcement, and to explore strategies to overcome these challenges. The research employs a sociological legal method. The findings indicate that law enforcement efforts in this context have not been fully effective. Although the police and related agencies have undertaken enforcement actions, prostitution under the cover of massage parlors continues to thrive. These establishments often offer hidden sexual services. Operators or pimps typically disguise these activities using coded language with regular clients or through closed digital communication networks. This demonstrates that pimps have developed more sophisticated and discreet operational systems that are difficult for law enforcement to detect directly. Several obstacles hinder effective law enforcement: First, massage parlors often continue operating covertly after being raided, simply by changing their business name, location, or service format. Second, the absence of consistent and routine monitoring by both law enforcement and regulatory agencies allows these operations to resume freely. Third, the lack of legal education and awareness programs at the community level contributes to public ignorance, making people less likely to participate in prevention or report prostitution-related activities. To overcome these challenges, several efforts are necessary. First, there must be strengthened administrative oversight and improved business licensing verification systems. Second, a joint task force comprising multiple government agencies should be established to conduct regular inspections and supervision of locations suspected of facilitating clandestine prostitution. Third, law enforcement and local governments should initiate community-based legal education programs, particularly in areas vulnerable to or near suspected prostitution sites.